The Relationship Between Children’s Scale Error Production and Play Patterns Including Pretend Play - Ishibashi, Mikako; Uehara, Izumi (Frontiers in Psychology, 2020)
Children of about two years of age occasionally make scale errors, e.g., they may attempt to fit their body into extremely small objects. Although previous studies have suggested that immature cognitive abilities may be responsible for these errors, the mechanism of scale error production is unclear. Because we assumed that obtaining characteristics of scale error behavior in the context of play would give us more useful indications concerning individual differences in producing scale errors, we examined how children engage in scale error behavior in relation to other types of play behavior, such as pretending, during the scale error task. The results indicate that children who produced scale errors exhibited less pretend play with miniature toys and tended to refuse to play with miniature toys more often than those who did not produce any scale errors during the task. Moreover, among the children who produced scale errors, the children who produced more scale errors were less likely to touch the miniature objects and less likely to perform pretending actions than those who produced fewer scale errors. These results suggest that pretense play is deeply related to a lower production, or no production, of scale errors. Some immature cognitive abilities underlining pretense play can be assumed to be related to the production of scale error. In conclusion, this study is one of the first to demonstrate empirically significant relationships between children’s scale error production and pretend behaviors, although further studies are necessary to understand the mechanisms